Arginine vasopressin (AVP) expressional changes in the hypothalamic paraventricular and supraoptic nuclei of stroke-prone spontaneously hypertensive rats - Yi, Sun Shin (Korean Association of Anatomists, 2012)
Arginine vasopressin (AVP) is a neuropeptide with vasoconstrictive, antidiuretic, cardiovascular regulative and hepatic glycogenolysis effects, that also affects other behaviors including modulating learning. A number of studies on AVP regulation have been conducted in various metabolic diseases (disorders). In this study, the immunoreactivities of AVP in the paraventricular nucleus (PVN) and supraoptic nucleus (SON) and mRNA expressions in the hypothalamus were investigated by immunohistochemistry and quantitative real-time PCR (RT-qPCR) in stroke-prone spontaneously hypertensive rats at different ages (i.e., at postnatal months [PM] 1, 8, and 12). Blood glucose levels in the PM 8 group were higher than in the other groups. However, cresyl violet positive neurons were detected in the PVN and SON of all animals, and numbers of cresyl violet positive neurons were similar in all aged groups. In addition, AVP immunoreactivity was detected in the PVN and SON of all age groups, and AVP immunoreactivity and mRNA expression levels were found to be increased in proportion to age by immunohistochemistry and RT-qPCR. These results suggest that the diabetic condition is temporally generated after hypertension has developed. Furthermore, our findings suggest that increased AVP expressions in the hypothalamic PVN and SON are associated with hypertension by age.